Graphene-Derived Carbon Support Boosts Proton Exchange Membrane Fuel Cell Catalyst Stability - Pavko, Luka; Gatalo, Matija; Finsgar, Matjaz; Ruiz-Zepeda, Francisco; Ehelebe, Konrad; Kaiser, Pascal; Geuß, Moritz; Dukic, Tina; Surca, Angelja Kjara; Sala, Martin; Bele, Marjan; Cherevko, Serhiy; et al. (ACS Catalysis, 2022)
The lack of efficient and durable proton exchange membrane fuel cell electrocatalysts for the oxygen reduction reaction is still restraining the present hydrogen technology. Graphene-based carbon materials have emerged as a potential solution to replace the existing carbon black (CB) supports; however, their potential was never fully exploited as a commercial solution because of their more demanding properties. Here, a unique and industrially scalable synthesis of platinum-based electrocatalysts on graphene derivative (GD) supports is presented. With an innovative approach, highly homogeneous as well as high metal loaded platinum-alloy (up to 60 wt %) intermetallic catalysts on GDs are achieved. Accelerated degradation tests show enhanced durability when compared to the CB-supported analogues including the commercial benchmark. Additionally, in combination with X-ray photoelectron spectroscopy Auger characterization and Raman spectroscopy, a clear connection between the sp(2) content and structural defects in carbon materials with the catalyst durability is observed. Advanced gas diffusion electrode results show that the GD-supported catalysts exhibit excellent mass activities and possess the properties necessary to reach high currents if utilized correctly. We show record-high peak power densities in comparison to the prior best literature on platinum-based GD-supported materials which is promising information for future application.
CRIS-Team WoS Importer:2022-08-26